2015
DOI: 10.1007/s13105-015-0433-9
|View full text |Cite
|
Sign up to set email alerts
|

Irisin, a unique non-inflammatory myokine in stimulating skeletal muscle metabolism

Abstract: Exercise offers several benefits for health, including increased lean body mass and heightened energy expenditure, which may be partially attributable to secretory factors known as myokines. Irisin, a recently identified myokine, was shown to increase metabolic rate and mitochondrial content in both myocytes and adipocytes; however, the mechanism(s) of action still remain largely unexplained. This work investigated if irisin functions by acting as an inflammatory myokine leading to cellular stress and energy e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 54 publications
(65 reference statements)
3
37
0
3
Order By: Relevance
“…These conflicting results might be attributed to the difference in experimental protocol or choice of anti-irisin antibodies [10]. Nevertheless, our study demonstrated that cAMP treatment increased both Fndc5 and Pgc-1α expressions in myotubes, probably because of longer stimulation (24 h) than in other in vitro models (1 h) [6,32].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…These conflicting results might be attributed to the difference in experimental protocol or choice of anti-irisin antibodies [10]. Nevertheless, our study demonstrated that cAMP treatment increased both Fndc5 and Pgc-1α expressions in myotubes, probably because of longer stimulation (24 h) than in other in vitro models (1 h) [6,32].…”
Section: Discussionmentioning
confidence: 56%
“…Irisin is one of the most prominent metabolic myokines that is generated from contracting muscle during exercise [31]. Previous studies have demonstrated that irisin stimulation increased the metabolic rate, mitochondrial content [6,32], and FFA oxidation in myocytes [3,7]. Moreover, a positive correlation of mortality risk in acute heart failure and serum irisin was also observed, suggesting irisin can be used as a predictive biomarker for cardiovascular diseases [33].…”
Section: Discussionmentioning
confidence: 98%
“…Analysis of the mouse Fndc5 gene promoter regions predicted a VDR:RXR binding site but not RAR:RXR or PPAR:RXR binding sites [30]. Interestingly, treatment with irisin increases mitochondrial oxidative metabolism, mitochondrial uncoupling and fatty acid oxidation in skeletal muscle cells [28, 29]. Thus, irisin induction may contribute, in a paracrine/autocrine manner, to the effects of ATRA treatment on C2C12 myocyte metabolism observed in the present work.…”
Section: Discussionmentioning
confidence: 75%
“…Reported effects of the myokine irisin favoring oxidative metabolism in skeletal muscle cells [28, 29] and WAT browning [3] are reminiscent of effects triggered by ATRA treatment. This, together with the fact that the promoter of the irisin precursor gene Fndc5 contains a RXR heterodimer binding site in the mouse [30], prompted us to study the impact of ATRA treatment on the production of irisin in skeletal muscle cells.…”
Section: Resultsmentioning
confidence: 99%
“…The main effects of irisin are the browning of white adipose tissue and increased energy expenditure. Irisin expression and/or circulating levels have been associated with anthropometric and biochemical parameters, other hormones and adipokines, and obesity, IR, type 2 diabetes and MetS (3,4).…”
Section: Introductionmentioning
confidence: 99%